TO KILL THE DROUGHT, NOT THE THIRST - THE PERSPECTIVE OF EUCLIDES DA CUNHA CONCERNING THE DESERTIFICATION - Jeane Medeiros Silva; Vânia Rubia Farias Vlach (Sociedade & Natureza)
Having the geographic space valued as a way of social understanding, conceptions about society relationships and nature concern to the Geography. As we consider the geographicity, conceptions on human interactions with space can be rescued from their significance means, being instituted in a historical and critical vision of the geographic space representations. The proposal of this work is to mediate a reflection between geographic spaceand language, focusing the desertification in the work ‘Os Sertões’1, by Euclides da Cunha,where in the first part, A Terra2, the writer presents some approaches directly concerned to the Geography, among which the desertification in the backlands of Brazil.For a theoretical-methodological contribution, our studies are based on the Discourse Analysis of French current to orientate the reflection on the corpus for analysis, (the text ‘Como se faz um deserto’3, from now on T1, the text ‘Como se extingue um deserto’4, T2, and finally, the text ‘O martírio secular da terra’5, T3), starting from the identified object (the fragment ‘A terra’, of Os Sertões), and also to restore the ideological formation of the conscious subjects during the passage from the 19th to the 20th century, what constitutes a certain thought on the Brazilian reality and on the movement of accusation that emerges from that process.